An Analysis of Introduction of Cloud Computing Affects the Corporate IT Shared Services Business Model - Liew, Chin Hoi (2013)
I.T. Shared Services is a global trend that is adopted by many companies’ especially global multi-national companies. The initial drivers of such services company setup is to around standardizing, consolidating and centrally manage I.T, this move would eventually bring cost reduction and saving to the company in long run. Today, business organizations are increasingly leveraging Shared Services to manage their I.T Infrastructure and application services with expectation further cost reduction and cost savings also expecting effectiveness and ability of business in expansion and competing in the market. Thus, with the introduction of Cloud computing in the real world experience suggest that cloud may mitigate certain technical issues and at the same time support business operation and increase agility of business and demand from business however the introduction of cloud computing may also impact or affect the business model and concept of the current I.T. Shared Services. I obtain findings based on in-depths interview with both Cloud service provider and key I.T. personnel from companies across various industries, I hope this research would bring valuable insights to both academics and practitioners who are interested in the studies of implication of cloud computing to Corporate I.T. shared services business model.